IoT Based Irrigation System - Kumar Yadav, Rajesh; Dev, Rishabh; Mann, Tushar; Verma, Tarun (International Journal of Engineering and Technology, 2018)
Availability of fresh water is one of the elementary conditions for life on Earth, however, water is a limited resource, which is now under an unprecedented pressure by global population growth, climate change and demand from several economic sectors. In particular, irrigated agriculture is one of the major water-consuming sectors. The aforementioned issues justify the need for a sustainable and rational use of water in irrigated crops.An IoT based irrigation system helps in supplying adequate amount of water to field and domestic crops in all seasons with minimum human interference. To deliver the required amount of water to the soil, we developed a system which works on the data obtained from the sensor nodes about the surroundings. The approach used helped in increasing the lifespan of the sensor nodes. Since the crop was being provided by adequate amount of water, the quality of crop increased.Â
Keywords: IoT; Irrigation System; lifespan of wireless sensor nodes; Micro-controller.